On the ejection of high velocity massive stars from star clusters - Ó Maoiléidigh, Cóilín (Trinity College (Dublin, Ireland). School of Physics, 2008)
OB1 runaways are massive, early-type, high velocity stars which have been ejected from their parent birthplaces. Some of which have velocities above 200km/s. Two mechanisms are plausible explanations for these objects: A supernova occurring in a binary system can often result in the system becoming unbound and the companion star being released from the system with a velocity comparable to its orbital velocity (SuperNova in a Binary scenario (SNB)); Close gravitational interactions between two or more stars can result in one or more of the stars being flung from the system with a high velocity (Dynamical Ejection scenario (DE)). Both of these mechanisms have been shown to exist in nature, however, which mechanism dominates the production of OB runaways is still unknown.
Keywords: Physics, Ph.D.; Ph.D. Trinity College Dublin